"Let's Chat": process evaluation of an intergenerational group chat intervention to increase cancer prevention screening among Vietnamese American families. Issue 3 (8th December 2020) - Duong, Huong T; Hopfer, Suellen
Abstract: Vietnamese Americans have a higher rate of cervical and colorectal cancer (CRC) compared to other ethnicities. Increasing CRC screening, Pap testing, and HPV vaccination is critical to preventing disproportionate cancer burden among Vietnamese families. To describe the successes and challenges of implementing a novel intergenerational family group chat intervention that encourages CRC screening, Pap testing, and HPV vaccination. Young adult Family Health Advocates (FHAs) were trained to facilitate online family group chat conversations to encourage cancer screenings. Ten families participated in a 4-week intervention. Data collection included screenshot data of family group chat conversations, family member surveys, and post-intervention FHA interviews. Intervention implementation successes included (a) cultural and language brokering, (b) active co-facilitation by family members to follow up on cancer screenings, (c) high levels of family group chat engagement, (d) high acceptability of intervention among families, and (e) accessibility of intervention curriculum. FHA challenges to implement the intervention included (a) sustaining cancer prevention conversations, (b) comfort with navigating family conversations around cancer screening, (c) relevance for all family members, and (d) missed opportunities for correcting misinformation. Researcher challenges included family recruitment and retention. The intervention made cancer-screening messages more accessible and was well accepted by Vietnamese families. Scaling up the intervention will require (a) training FHAs to monitor family conversations and build confidence in sharing medical accurate messages, (b) segmenting group chats by age and gender, and (c) employing multiple family engagement strategies.